The Temporalities of the Market - Miyazaki, Hirokazu (American Antropological Association, 2003)
Social theorists' recent interest in global capitalism is partially driven by their sense of "being behind" in a changed and changing world. It is also part of their larger efforts to critique the present. In this article, I seek to find analogues of this sense of temporal incongruity between knowledge and its objects in the Tokyo financial markets. My focus is on the anxieties and hopes animating some Japanese securities traders' life choices. I argue that these traders' differing anxieties and hopes resulted from their divergent senses of the temporal incongruity among trading strategies, workplaces, and Japan's national location visÐaÐvis the United States. Drawing on a parallel between social theorists' and traders' efforts to generate prospective momentum in their work, I propose that anthropologists investigate the work of temporal incongruity in knowledge formation more generally